Typology of 21st Century Islamic Boarding School Education (Pesantren) in Indonesia - Fathoni (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research examines the dynamics of Islamic boarding schools in Indonesia with a focus on typology and development. Through a qualitative descriptive approach and library research, this research identified three developing typologies of Islamic boarding schools: Salaf Islamic Boarding Schools, Modern Islamic Boarding Schools, and Radical Islamic Boarding Schools. Salaf Islamic boarding schools, which are traditional Islamic boarding schools, maintain the teaching of classical Islamic books without adding to the general curriculum. The case study of the Tarbiyatun Nasyi'in Islamic Boarding School in Jombang provides an illustration of the sustainability of the Salafist model which still exists today. Modern Islamic boarding schools, represented by Pondok Modern Gontor, show transformation by incorporating a general curriculum, emphasizing Arabic and English language teaching, and managing Islamic boarding school management neatly. This phenomenon illustrates the adaptation of Islamic boarding schools to the demands of the times and general education. Radical Islamic boarding schools reflect a conservative and scriptural Islamic ideology, often involving fundamentalist views and radicalism. Case studies of Islamic boarding schools in Lamongan and Ngruki highlight the negative impact of radical thinking in the students' thinking patterns and the involvement of some alumni in acts of terrorism. This research describes the variations in educational approaches and religious views in Islamic boarding schools, reflecting the dynamics of Islam in Indonesia. With a deeper understanding of Islamic boarding school typology, this research contributes to detailing the development and role of Islamic boarding schools in shaping Islamic society in Indonesia